Патоморфологічна характеристика церебральних мікросудин у хворих на цукровий діабет II типу, ускладнений ішемічним півкульовим інфарктом мозку - Авраменко, Юлія Миколаївна; Avramenko, Y. M. (Запорізький державний медичний університет, 2021)
При ЦД-2, в порівнянні з УК і ДІЕП, мікросудини ММО і кори ГМ мають потовщені стінки через просочення плазмою і гіаліноз, вищі індекси Вогенворта, Керногана і рівні апоптозу ендотелію (за рівнем експресії каспази-3), вищу щільність судин в корі ГМ і меншу кількість перицитів в капілярах; в ГМ має місце вища експресія VEGF і VEGFR-2 та співвідношення MMP-9/TIMP-1, збільшена площа колагену 4 типу. За даними ЕМ має місце апоптоз перицитів і ендотелію, розширені базальні мембрани містять колаген і щільні аморфні маси. Над півкульовим інфарктом ГМ на тлі ЦД-2 артеріоли мають більш товсті стінки і вищий індекс Вогенворта, а потовщені капіляри - менше число перицитів (ніж при інфаркті на тлі ЦА). В корі ГМ над інфарктом визначаються поодинокі бруньки росту капілярів та підвищена експресія VEGF і VEGFR-2. In deceased patients with diabetes mellitus type 2 (DM-2) in the arterioles and capillaries of the pial meninges (PM) and cerebral cortex (CC) is determined by uneven thickening of the inner elastic membrane and basement membrane, respectively, with the accumulation of PAS-positive material, uneven thickening of the vascular wall due to plasma permeation that progress to hyalinosis with loss of smooth muscle cells. According to digital morphometry, the arterioles of the PM and the arterioles and capillaries of the CC have a greater vascular wall thickness, as well as significantly higher Wogenworth and Kernogan indices. In DM-2, an increase in the level of vascular endothelial apoptosis (by the level of expression of caspase-3) stimulates increased expression of survival factor VEGF and VEGFR-2, a significant increase in the expression ratio of MMP-9/TIMP-1, which creates conditions for destruction of the intercellular matrix and the development of fibrosis of PM and cortical microvessels, which confirms enlarge area expression of collagen type 4. According to EM, apoptosis of pericytes and single endothelial cells is observed in capillaries, as well as widespread and significant expansion of basement membranes with the accumulation of electron-dense amorphous material and collagen fibrils. The number of pericytes in the thickened walls of capillaries is significantly lower, and the density of microvessels in the CC is statistically significantly higher than in the conditional control group and the group dyscirculatory-ischemic encephalopathy. The development of ischemic hemispheric infarction in patients with DM-2 leads to change the parameters of the microvessels of the PM and CC: arterioles have a significantly thickened wall and increased outer and inner diameter, as well as increased Wogenworth index and significantly thickened capillaries due to hyalinosis with a reduced number of pericytes. According to the IHC study of hemispheric cerebral infarction observed significantly higher expression of VEGF, VEGFR-2, the ratio of MMP-9/TIMP-1 expression, which stimulates neoangiogenesis directly in the periinfarction zone, while in the CC over necrosis single buds of capillary growth and a tendency towards a decrease in vascular density (compared with the DM-2 group).
Pathomorphological characteristics of cerebral microvessels in patients with diabetes mellitus type II complicated by ischemic cerebral infarction
Keywords: цукровий діабет; ішемічний інфаркт; артеріоли; капіляри; м’яка мозкова оболонка; CD31; CD105; VEGF; VEGFR-2; MMP-9; TIMP-1; Ki-67; каспаза-3; колаген IV типу; diabetes mellitus; ischemic infarction; arterioles; capillaries; pial meninges; caspase-3; type IV collagen